3β-Acet-oxy-lup-20(29)-en-28-yl 1H-1,2,4-tri-azole-1-carboxyl-ate - Santos, R. C. (2010)
The title triterpene, C(35)H(53)N(3)O(4), is a C-28 carbamate derivative of 3β-acet-oxy-betulin prepared in a one-step reaction from the commercially available 1,1'-carbonyl-di(1,2,4-triazole) (CDT), crystallized from acetone/n-hexane. All rings are trans fused. The carbamate and acetate substituents are in axial and equatorial positions, respectively. A quantum chemical ab initio Roothaan Hartree-Fock calculation of the equilibrium geometry of the isolated mol-ecule gives values for bond lengths and valency angles in close agreement with experimental values. The calculation also reproduces the observed mol-ecular conformation, with puckering parameters that agree well with those determined from the crystallographic study.